2011
DOI: 10.1016/j.ajpath.2010.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Mycobacterial Granuloma

Abstract: The granuloma, a hallmark of host defense against pulmonary mycobacterial infection, has long been believed to be an active type 1 immune environment. However, the mechanisms regarding why granuloma fails to eliminate mycobacteria even in immune-competent hosts, have remained largely unclear. By using a model of pulmonary Mycobacterium bovis Bacillus Calmette-Guerin (BCG) infection, we have addressed this issue by comparing the immune responses within the airway luminal and granuloma compartments. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 68 publications
(90 reference statements)
1
17
0
Order By: Relevance
“…Conversely, Th2 cytokine IL-10 inhibits T cell proliferation by down regulating the production of IL-2 [11]. IL-10 is also known to contribute significantly to formation of a disorganized granuloma [2,12]. Several studies have demonstrated the immunosuppressive role of IL-10 cytokine in human and animal models [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Th2 cytokine IL-10 inhibits T cell proliferation by down regulating the production of IL-2 [11]. IL-10 is also known to contribute significantly to formation of a disorganized granuloma [2,12]. Several studies have demonstrated the immunosuppressive role of IL-10 cytokine in human and animal models [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, high levels of IL-10 are found in lungs, serum, sputum, and bronchoalveolar lavage (BAL) fluid of patients with pulmonary tuberculosis (TB) (4,56). There are data suggesting a necessary role in control of TB (57)(58)(59)(60)(61), while others suggest that IL-10 plays no part in the dynamics (62)(63)(64)(65)(66)(67)(68). Our modeling studies predict a protective role for IL-10, balancing inflammation, limiting tissue damage, and regulating the dominant macrophage phenotype in the lymph node and lung (69)(70)(71).…”
mentioning
confidence: 99%
“…Mtb uses a variety of evasion strategies to resist attack from the host immune system, by blocking phagolysosome fusion and detoxifying reactive oxygen and nitrogen radicals [29]. In addition, virulent Mtb has multiple strategies to delay the early initial induction of T cell responses or to modulate antigen presentation to CD4+ T cells [27,29].…”
Section: Overview Of Tb Pathogenesismentioning
confidence: 99%